Efficacy of Cangrelor as Bridging Therapy Post PCI - Khan, Abdul A.; Murtaza, Ghulam; Khalid, Muhammad; Finniss, Mathew; Helton, Thomas (Cardiovascular & Haematological Disorders - Drug Targets, 2020)
Background: Dual antiplatelet therapy (DAPT) remains the cornerstone management for the prevention of acute stent thrombosis after percutaneous intervention (PCI). Situations mandating early interruption of DAPT carry a high risk of ischemic complications. Perioperative bridge therapy using Cangrelor, an intravenous P2Y2 inhibitor, may offer a potential solution. Unfortunately, evidence for its use in non-cardiac procedures is limited. Methods: Our protocol demonstrates successful off-label use of IV Cangrelor bridge therapy in a non-cardiac surgery patient. We describe a case of a 77-year old male; triple therapy with Aspirin, Apixaban, and Ticagrelor for recent drug-eluting stent placement required immediate surgical resection of stage I colonic adenocarcinoma. Results: Cangrelor bridge therapy was utilized both preoperatively and postoperatively without ischemic or bleeding complications. The patient tolerated exploratory laparoscopic colectomy with minimal bleeding and good post-op recovery. Conclusion: Minimizing the interruption of DAPT therapy in high-risk patients is achievable. However, careful planning with a team-based approach involving surgeons, cardiologists and pharmacists, along with close clinical follow-up and vigilant management of anti-platelet therapy is recommended.
Keywords: antiplatelet